2018
DOI: 10.1007/s00264-018-4096-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain control following arthroscopic rotator cuff repair: peri-articular injection versus interscalene brachial plexus block

Abstract: Although IBPB provided superior pain control during the initial few hours after ARCR surgery, PI was superior from 16 to 24 hours post-operatively. The rates of side effects, such as nausea and temporary arm numbness, were also lower in the PI group than in the IBPB group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Cryotherapy, ice wrap, and subacromial injection/infusion have been used for postoperative pain control in ARCR surgery, but the effectiveness of each is still controversial [1,[3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryotherapy, ice wrap, and subacromial injection/infusion have been used for postoperative pain control in ARCR surgery, but the effectiveness of each is still controversial [1,[3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…In the SI group, a significant improvement in the VAS score (compared to the preoperative VAS) was seen earlier than in the ice wrap group. Saito et al [3] stated that SI had a slow analgesic effect (this effect was not felt until the day after surgery), which could cause problems when SI is used to control acute postoperative pain. Cho et al [31] mentioned that SI had a significant analgesic effect 3 days after surgery compared to a placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and others reported that the effect of ISB weans after 6 hours. [5][6][7] ISB is ineffective especially when administered after a prolonged postoperative duration, and when the pain relapses.…”
Section: See Related Article On Page 1243mentioning
confidence: 99%
“…The authors performed an observational study on 997 patients undergoing outpatient orthopaedic surgery and concluded that marijuana use was an independent factor associated with less pain intensity in the operative site. The authors should be applauded for performing a well-designed study in an important topic (e.g., acute pain) in patients undergoing orthopaedic surgery [2,3]. The need to improve post-operative recovery by reducing moderate-to-severe post-operative pain makes the topic very important in peri-operative medicine [4,5].…”
mentioning
confidence: 99%